Do controlling shareholders' equity pledges affect M&A investment? evidence from listed companies in China - Duan, Qianqi; Mohd Nor, Normaziah; Selamat, Aslam Izah (Asian Economic and Social Society, 2023)
As a new financing method, equity pledges are popular in Chinas capital market. With the emergence of new financing models, will the relationship between financing and investment in corporate financial management change? The purpose of this study is to determine whether the controlling shareholders' equity pledges affect corporate merger and acquisition (M&A) investment decisions. This paper uses data for listed companies from the China Stock Market & Accounting Research (CSMAR) database, and Stata 17 is used as the data processing software. The M&A variable is virtual and uses the logit model to study the relationship between controlling shareholders' equity pledges and M&A investments. To test the robustness of the results, we replace the key variables, transform the model, and use the Gaussian Mixture Model (GMM) method to obtain the same results. The study found a positive correlation between controlling shareholders' equity pledges and M&A investments. Further cross-sectional study shows that the positive correlation is stronger in state-owned companies, non-manufacturing companies, and companies with low pledge ratios. This study is conducive to standardizing the equity pledge behavior of listed companies and safeguarding the interests of investors.